Makna Hijab dalam Al-Qur’an - Afif Arrasyidi; Afwan Abdul Hakim KH; Agung Fauzan; Aria Rahman; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
Trend fashion clothing is currently experiencing significant developments, especially in the field of women's hijab. This development certainly inspires women to wear the hijab, but the use of the hijab is not only limited to covering the genitals but also following the elements of fashion in it. This research aims to introduce us to the development of the hijab itself as well as current issues surrounding the hijab and how the Qur'an reacts to it. This research uses the maudu'i (thematic) method which is entirely a qualitative research. The results and discussion cover the current hijab phenomena, knowing what veils, headscarves and burqas are, knowing the history of hijab in pre-Islamic and post-Islamic times, and knowing the problems faced regarding hijab at this time. The benefits of research are to add insight regarding the problems faced with hijab and how the Qur'an reacts to them and also become an additional reference for future researchers who research hijab.